2019
DOI: 10.1002/lary.28429
|View full text |Cite
|
Sign up to set email alerts
|

The submental flap for head and neck reconstruction: Comparison of outcomes to the radial forearm free flap

Abstract: Objectives To compare intraoperative, postoperative, functional, and oncologic outcomes of the submental island pedicled flap (SIPF) to the radial forearm free flap (RFFF). Study Design Retrospective review; comparison with statistical analysis. Methods A retrospective review was performed on patients at two tertiary care academic hospitals by a single surgeon. Consecutive patients who underwent cancer resection and reconstruction with SIPF or RFFF between 2004 and 2016 were included. Cancer staging, surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…The SAIF has been shown to compare favorably with free flaps in terms of operative time and LOS 1,5 . The SAIF is equivalent to free flaps in terms of rate of flap failure and revision as well 5 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SAIF has been shown to compare favorably with free flaps in terms of operative time and LOS 1,5 . The SAIF is equivalent to free flaps in terms of rate of flap failure and revision as well 5 .…”
Section: Discussionmentioning
confidence: 99%
“…While free tissue transfer remains the workhorse for reconstructing large defects of the head and neck, the SAIF has demonstrated value for a variety of reconstructive challenges. In comparison with free flaps, the SAIF offers lower procedural time and hospital length of stay (LOS) 1,5 . Harvest is technically straightforward, and donor‐site morbidity is minimal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this study included patients with primary cancers in salivary glands, paranasal sinuses, skin, and oropharynx which might have a less aggressive nature and recurrence potential compared to oral cavity cancers. 31 Chang, Asarkar, and Nathan published a comprehensive review in an attempt to resolve the controversy surrounding the use of the SIF in oral cavity cancer and concluded that it is oncologically safe to use in N0 neck. However, regarding its use in the presence of positive neck nodes, there were limited quality data supporting this with reasonable oncologic safety that was at risk of selection bias.…”
Section: Discussionmentioning
confidence: 99%